A Technique of Crossover and Mutation to solve School Time Table Problem using Genetic Algorithm - Irfan, Mohd (International Journal of Computer Sciences and Engineering, 2019)
Creating school time table lies under the category of NP hard problems. If we try to create a time table using exhaustive approach i.e applying all possible combinations, then it can take a huge amount of time to solve the problem. So Genetic Algorithm is a good way to solve such problems. Instead of using traditional techniques of Crossover and Mutation in genetic algorithm we have applied a better technique of crossover and mutation which reduces the search space by deducting invalid time tables from the search space. We have also done some experiments which show the variation of number of generations to solve the problem with mutation rate.